Development of Protein Synthesis Topic Webtoon “Synprory!” Learning Media to Improve Understanding of 12th Grade High School Student - Cricilia, Tyas; Ratnasari, Evie (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2024)
The development of science and technology is increasingly rapid in the world, especially for the educational sector, the teachers should keep up with the times and adapt to the current technology. This can be utilized by teachers to start innovating by creating a learning media that students may access through their smartphones anytime and anywhere. One of the topics considered difficult to learn is protein synthesis, because it is not sensory and complex. This research aims to develop webtoon-based web-comic learning media to improve understanding of the 12th grade student in protein synthesis sub-topic. This research used ASSURE method (Analyze Learner, State Objective, Select Media and Materials, Utilize Media and Materials, Require Learner Participant, and Evaluate and Revise). Data collection methods through validation methods, response questionnaires, pre-test and post-test which were carried out 20 grade 12th students of SMA Negeri 14 Surabaya. The data obtained were analyzed using descriptive-quantitative techniques. The results of this study is a learning media “Synprory!” webtoon-based web-comic with validity value 3,88 considered as a valid category and gain a positive responses from student with a practicality value of 95,5%. The results of the study were also effective in improving student understanding with an N-gain of 0,77 in the high category. Thus the development of “Synprory!” webtoon-based web-comic learning media to improve understanding of the 12th grade protein synthesis sub-topic is feasible in terms of validity, practicality, and effectiveness.